Advancing skill development for business managers in industry 4.0 emerging research and opportunities - Fazzin, Sara, 1982- (Advances in logistics, operations, and management science (ALOMS) book series., 2020)
"This book explores Industry 4.0 and the important tech apps that revolutionize and disrupt the modern organization, such as artificial intelligence, machine learning and programming languages"--